Assessment of nutritional status by dual X-Ray absorptiometry in women with rheumatoid arthritis: A case–control study. Issue 6 (February 2019) - Reina, Delia; Gómez-Vaquero, Carmen; Díaz-Torné, Cesar; Solé, Joan Miquel Nolla
Abstract : Abstract: Rheumatoid arthritis (RA) has been related to an impairment of the nutritional status. Body mass index (BMI) has been used but questions arise about how to properly evaluate nutritional status in RA patients. Few studies have evaluated it by dual-energy X-ray absorptiometry. In women with RA, to analyze: their nutritional status compared to that of a control population, differences between the prevalence of impairment of nutritional status measured by dual energy X ray absorptiometry (DXA) and by classical methods used in clinical care, determinants of nutritional status, prevalence of sarcopenia. Case–control study including 89 women with RA. The control group was composed by 100 patients affected by non-inflammatory rheumatic disorders. Study variables included age, RA duration, history, activity and disability, and in relation to nutritional status: BMI, serum albumin (ALB), whole body DXA assessment, and skeletal muscle index (SMI). Mean age of patients was 62 ± 8 years, mean duration of RA was 14 ± 9 years, mean disease activity score (DAS28) was 3.7 ± 1.4 and mean Health Assessment Questionnaire was 0.88 ± 0.77. BMI was 27.43 ± 5.16 Kg/m 2 in patients and 27.78 ± 3.98 Kg/m 2 in controls ( P : ns). ALB was within normal range in all patients. By whole body DXA, RA patients presented a statistically significant lower lean mass in all locations and lower fat mass in limbs than controls. Patients had a redistribution of fat mass to trunk. Lean mass directly correlated with fat mass. Neither BMI nor ALB correlated with DXA parameters. BMI, appendicular lean mass and SMI correlated inversely with disease duration. Trunk lean mass correlated inversely, and fat mass directly, with RA disability parameters. RA patients fulfilled criteria of sarcopenia in 44% of cases versus 19% of controls ( P <.001). In RA patients, regarding SMI, BMI showed a high specificity to detect sarcopenia (94% of the patients with low BMI had sarcopenia) but low sensitivity (47% of the patients with normal BMI or overweight had sarcopenia). RA patients have an impairment of nutritional status associated to disease duration that looks like sarcopenia and that is not predicted by BMI.